Increasing CD8+ T cells and pro-inflammatory cytokines is associated with hypersensitivity reactions in people living with HIV-1 under antiretroviral treatment - ADECHINA, Adefounke Prudencia; ASSOGBA, Pierrot Yaou; TCHIAKPE, Edmond; Nouatin, Odilon Paterne; MOUTAIROU, KABIROU; Fievet, Nadine; DECHAVANNE, Célia; YESSOUFOU, AKADIRI (My University, 2023)
Background: Despite their good efficacy, antiretroviral drugs often induce adverse effects, in particular hypersensitivity reactions (HSR) which cause significant discomfort leading to the abandonment of treatment and then to therapeutic failure in some HIV-positive patients. Therefore, in this study, we aimed to assess the association between immune responses and hypersensitivity reactions (HSR) induced by antiretroviral treatment in people who living with HIV-1 (PLHIV-1), through the distribution of immune cells and cytokine profiles. Methods: PLHIV-1 were enrolled at two reference centers in Benin. Clinical data, therapeutic line and adverse reactions were recorded. Serum cytokine levels were determined by ELISA and immune cell frequencies by immunophenotyping using flow cytometry. Results: 98 PLHIV-1 individuals aged between 30 – 50 years old were enrolled, including 71% female, 30% who developed HSR and all were under TDF+3TC+EFV therapeutic line at inclusion date. We observed an increase in IFN-γ levels and conversely a significant decrease in IL-4 in PLHIV-1 who developed HSR. In addition, pro- and anti-inflammatory cytokines (TNF-α, IL-5, IL-6 and IL-13) increased in all PLHIV-1, concomitant with a shift of Th1/Th2 ratio to Th1 phenotype, especially in those who developed HSR. Besides, CD4+ T cell frequencies decreased while those of CD8+ T cells increased in all PLHIV-1, and especially in those who developed HSR. NK and NKT cells frequencies significantly decreased in all PLHIV-1. Conclusion: Our study showed that immune status of PLHIV-1 having developed ART-associated HSR was linked to an increase in CD8+ T lymphocytes correlated with a proinflammatory Th1 phenotype despite a decrease in CD4+ T lymphocytes and low level of circulating IL-4. These results suggested a decrease in humoral response and in favor of cellular response characteristic of type IV hypersensitivity reactions. Such immune parameters might also show a prognostic power of HSR in PLHIV-1 and the results would better guide clinicians to improve the management of PLHIV-1.
Keywords: PLHIV-1; Antiretroviral therapy; Hypersensitivity reactions; Immune cells; Cytokines.